الخدمة المرجعية الرقمية : مفهومها ، وأساليب تقديمها مع تقديم مقترح لإنشائها في المكتبة المركزية لجامعة الموصل - الخفاف، سمية يونس سعيد (جامعة الموصل - كلية الآداب, 2012)
The study aims at defining the digital reference, its concept, purpose, motives, as well as studying the reference deportment at University of Mousl Central Library', its past present and then presenting a proposal to initiate a digital reference service at this library with the requirements needed to activate that. The study arrived at the following results \ 1-\ The\ reference collection of University of Mosul central Library is in an urgent need for updating so as to offer better information service. \ 2-\ The\ absence of specialized staff (Reference Librarians) holding a degree information and librarianship at the library reference department has a negative effect on service offered. \ 3-\ Initiating\ a digital reference service at the library' will help in offering information service which copes with the new developments in this specialization to satisfy the user's needs. \ 4-\ The adaptation of digital reference services at University of Mosul central Library.
747748
Keywords: الانترنت -- الخدمة المرجعية الرقمية -- خدمات البيانات -- المكتبة المركزية -- المكتبات -- جامعة الموصل -- الخدمات المكتبية -- تكنولوجيا المعلومات -- المصطلحات -- الحاسبات الألكترونية